(untitled) (Bangladesh Medical Journal Khulna, 2020)
Background: The unsolicited practice for self medication is commonly seen all over the world. In our country it is also commonly practiced even by health care professionals. Objectives: This study is done to focus on the prevalence and other associated factors in various aspects of self medication among medical students. Methods: This was a descriptive study conducted within 4th year students among 113 participants by using a researcher made questionnaire in Gazi Medical College, Khulna from January 2019 to June 2019. Data analysis was done by using Microsoft excel. Results: The prevalence of self medication was reported at 88.49%. The most important reasons for self medication was previous experiences with the illness (48%), minor illness (30%), and time saving (25%). The greatest number of students used self medication to treat headache (30%), gastric acidity (28%), fever (22%), and runny nose (14%). The data reveals that the highest proportion (38%) of students learned medications from old prescription of doctor provided to cure their past illness. The respondents used different group of drugs where greatest number (32%) used analgesics followed by anti ulcerants (28%), antipyretics (25%), and antibiotics (22%). Conclusion: Due to high prevalence of self medication, it is necessary to implement strict rules and regulations to prevent this practice and provide adequate facilities to access medical services properly. Bang Med J (Khulna) 2019; 52 : 21-24